2015
DOI: 10.1111/cgf.12564
|View full text |Cite
|
Sign up to set email alerts
|

Content‐Independent Multi‐Spectral Display Using Superimposed Projections

Abstract: Figure 1: (a) Multi-spectral display system setup with three modified conventional 3-primary projectors, a conventional LCD 3-primary projector for comparison and a high spatial and spectral resolution spectroradiometer (SOC-730 hyperspectral camera) for measurements. (b)The candidate set of 30 primaries used for our prototype, (c) the existing r, g and b filters of the projectors, (d) the 9 filters chosen by our algorithm, (e) the 9-primaries generated by multiplying the r, g and b primaries with the 9 chosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…We showed that our modular architecture based on relay optics could support the extension of projector performance beyond the capability of projector hardware and, in particular, the HDR projection. The modular architecture would allow us to build other types of high performance projection systems, such as multi-band projection, by combining more than two display panels with slightly different spectral properties [41]. However, adding optical components also leads to additional aberrations and reduction of peak luminance.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that our modular architecture based on relay optics could support the extension of projector performance beyond the capability of projector hardware and, in particular, the HDR projection. The modular architecture would allow us to build other types of high performance projection systems, such as multi-band projection, by combining more than two display panels with slightly different spectral properties [41]. However, adding optical components also leads to additional aberrations and reduction of peak luminance.…”
Section: Discussionmentioning
confidence: 99%
“…However, while these reproduce an acceptable metameric spectrum as perceived by the CIE standard observer, it is generally a low fidelity approximation of the real spectrum which is not correct for other observers. Li et al take an opposite strategy, i.e., explore the use of wide band primaries for accurate spectral reproduction [LMLG15] (cf. Figure ).…”
Section: Hardwarementioning
confidence: 99%
“…Multispectral projection system using superimposed projectors with varying wide‐band spectral color filters. [LMLG15]. In comparison with a standard LCD projector, the color saturation and color gamut is enhanced.…”
Section: Hardwarementioning
confidence: 99%
“…Multi-primary displays usually aim for a wide color gamut, as perceived by a human observer. Related algorithmic problems include selecting the optimal color primaries [Ben-Chorin and Eliav 2007;Long and Fairchild 2011;Li et al 2015] as well as gamut mapping (e.g., [Banterle et al 2011]), where pixels of an image are processed to fit within the fixed gamut provided by a display. Gamut expansion can also help to optimize image presentation with large-gamut displays [Majumder et al 2010].…”
Section: Spectral Displays and Algorithmsmentioning
confidence: 99%
“…For example, we demonstrate a custom-built hyperspectral projection system that is closely related to the design introduced by Rice et al [2007] and later used by Mohan et al [2008] in the supplemental document. Hyperspectral projectors could achieve simultaneous color and spectral match of displayed target content, which may be beneficial for some applications [Li et al 2015].…”
Section: Spectral Displays and Algorithmsmentioning
confidence: 99%